Two types of laminolysis in adolescent athletes - Miyagi, Ryo; Sairyo, Koichi; Sakai, Toshinori; Yoshioka, Hiroshi; Yasui, Natsuo; Dezawa, Akira (Journal of orthopaedics and traumatology, 2012)
Bony defects in the spine are divided into three main types: spondylolysis, pediculolysis, and laminolysis. Lumbar spondylolysis is a well-known stress fracture that occurs frequently in adolescent athletes. Pediculolysis means stress fracture of the pedicle, which sometimes occurs subsequent to unilateral spondylolysis. Laminolysis is a rarely reported stress fracture similar to spondylolysis and pediculolysis that sometimes causes low back pain (LBP). However, its pathomechanism has not been elucidated. Recently, we encountered four adolescent athletes with symptomatic laminolysis. Mean age was 15.8 (range 15–17) years. All subjects reported severe LBP exacerbated by extension of the lumbar spine, and radiology revealed two types of laminolysis: hemilaminar type and intralaminar type. To elucidate the mechanisms of each type, we reviewed a biomechanical study, and found that the hemilaminar type was thought to be subsequent to contralateral spondylolysis, while the intralaminar type might be a result of a stress fracture due to repetitive extension loading.